Change in the role of cities in China's air transport 2005–2015. Issue 1 (2nd January 2018) - O'Connor, Kevin; Fuellhart, Kurt; Zhang, Shengrun
ABSTRACT: Air transport has been expanding rapidly in China over the past decade. That growth corresponded with economic development as well as liberalization in the regulations surrounding airline operations and city and provincial responsibilities for air transport infrastructure. This paper analyses the way the airline industry responded to those changes by identifying the rank of 37 cities on a series of measures of airline operations in 2005 and 2015. Results show that the ranks of the seven leading cities remain unchanged, and only a small change has been recorded on each of the measures at other cities over this time period. The results suggest that there is a level of inertia in the overall geography of China's air transport. Closer attention to the activity of the airlines, with particular attention to small and large airlines, as well as those within corporate groups will be an important direction in future research.